The Role of Entrepreneurial Orientation and Competitive Intelligence In The Influence of Strategic Flexibility on Organizational Agility - Sentoso, Antony; Ong, Jovi; Nelson, Alden (Universitas Muhammadiyah Sorong, 2025)
Entrepreneurial orientation and competitive intelligence play an important role in influencing the strategic flexibility and organizational agility. Therefore, we need to know what kind of orientation and competitive intelligence that suit the most for the organization. This research aims to analyze the role of entrepreneurial orientation and competitive intelligence in the influence of strategic flexibility on organizational agility. The research method used is a quantitative method, with data collection through distributing questionnaires to respondents who are working in the hotel industry. From the research result all the hypotheses all are accepted and effect significantly positive between each variable. This research highlights the importance of entrepreneurial orientation and competitive intelligence in increasing the strategic flexibility and organizational agility of an organization so that the organization has an innovative and unique strategy from other organizations. The implications of this research suggest that organizations should prioritize these factors to stay competitive in an increasingly dynamic market. Future research should explore additional samples and variables and investigate these relationships in different industries to deepen the understanding of the factors influencing strategic flexibility and organizational agility